Pemanfaatan Big Data Dalam Diagnosis Penyakit Jantung Koroner - Resti Yulianda Putri (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Coronary heart disease is no stranger to people around the world. This disease must be watched out for because it is the number one cause of death in the world. Early diagnosis is necessary to reduce the risk of this heart disease. Therefore, data sources are needed to help diagnose heart disease patients. One data source that can be used is big data. The aim of this paper is to explain the use of big data in the diagnosis of coronary heart disease. Through a literature review about big data and coronary heart disease, it is known that the help of big data can help in diagnosing disease quickly and accurately with algorithms that will suggest the most likely diagnosis. Although challenges such as data security and ethics of use must be taken into account, the enormous benefits offered by the integration of big data in the medical world make it an invaluable tool to support efforts to prevent and treat heart disease.